ILRI financial statements 2007 - International Livestock Research Institute (International Livestock Research Institute, 2008)
The ILRI financial statements for the year ended 31 December 2007 starts with statement of purpose, statement by the chairman of board of trustees, board statement on risk management and statement of management's responsibilities. It then presents consolidated and institute statements and four exhibits. The first one, statement of activities outlines revenue and gains, expenses and losses, and expenses by natural classification. The second statement, financial position, presents assets, liabilities and net assets. The third and the fourth statements are statements of changes in net assets and statement of cash flows respectively. The document continues with notes to the consolidated financial statements and ends with ends with exhibits on schedule of unrestricted grant revenue, schedule of program restricted grant revenue, schedule of furnishings and equipment, and schedule of direct and indirect cost rates.